The construction of an ecological security pattern based on the comprehensive evaluation of the importance of ecosystem service and ecological sensitivity: a case of Yangxin County, Hubei Province - Xu, Hong; Zhang, Zhiqi; Yu, Xincan; Li, Tianyue; Chen, Zheng (Frontiers in Environmental Science, 2023)
Ecological safety pattern is the basic guarantee for pollution control, ecological environmental protection, economic construction and sustainable social development, and is an important means of integrated and coordinated development, protection and governance. This study proposes a research method to identify ecological source sites based on the evaluation of the importance of ecosystem services and ecological sensitivity, and to identify ecological corridors using the minimum cumulative resistance model. And the empirical analysis was carried out in Yangxin County, Hubei Province as an example. The results show that the study area has 16 key corridors and 29 potential corridors, a total of 45 ecological corridors, with a total length of 452km. In addition, these ecological corridors present a network-like intertwined distribution, connecting various ecological source sites, ensuring the connectivity between ecological source sites, while the well-developed water source sites in the study area provide excellent ecosystem service functions such as water containment for the area.